Facilitator's guide: Participatory Foresight on Gender Equality in Agri-food Systems - Malhotra, Aayushi; Puskur, Ranjitha; Anabacha, A.; Kori, Pooja; Verma, Benu; Shah, C.; Bisht, S.; Samal, S.; Rawat, A.; Bhandari, B.; Maheshwari, M. (CGIAR GENDER Impact Platform, 2025)
The Evidence Module of the CGIAR GENDER Impact Platform collaborated with Institute of Himalayan Environmental Research and Education (INHERE) to develop a participatory foresight methodology for gender equality in diverse agrifood systems. This methodology was tested during the participatory workshops conducted across two states i.e. Uttarakhand and Odisha, in India. Workshops were attended by a diverse group of participants, including men and women farmers, members of farmer producer organisations (FPOs), community health and rural development workers, local leaders and government officers, women’s self-help group (SHG) members, migrant workers, agri-business representatives, and academic researchers. The aim of this engagement was to understand the current conditions of gender dynamics within agricultural households while also identifying diverse perspectives on gender equality among other stakeholders. Workshops also provided an opportunity to identify existing and potential drivers of change in agri-food systems, and consequently their impact on food and nutrition security across involved communities. Based on the learnings from these workshops, this trainer’s guide is designed to provide a structured approach to understanding and addressing gender disparities, utilizing foresight methodologies to envision equitable futures across agri-food systems. It outlines practical steps for conducting participatory workshops focusing on two key questions: how to engage local stakeholders in exploring plausible futures for equitable agri-food systems, and how to broker and catalyse collaborative plans of action based on the foresight analysis.